Analysis of Collaboration Between the Ministry of Women's Empowerment and Child Protection and the Surabaya DP3APPKB in the PUSPAGA Program - Yuan Dwi Arimulani; Syahrani Adilla Arifin; Amelia Imro'atu Sholehah; Putri Salma Nur Hanifiah (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
Gender equality, as articulated in Sustainable Development Goal (SDG) 5, remains a major policy challenge in Indonesia, including the City of Surabaya. According to the 2025 SIMFONI-PPA database, 1,319 cases of violence against women were recorded in East Java, with domestic settings accounting for the majority of incidents. This study analyzes the implementation of intergovernmental relations (IGR) between the Ministry of Women's Empowerment and Child Protection (PPPA) and the Surabaya Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3APPKB) through the Family Learning Center (PUSPAGA) program in addressing domestic violence and promoting gender equality. This study employed a qualitative descriptive approach based on a literature review using Wright's (1988) Intergovernmental Relations framework, which comprises five analytical dimensions: All Units of Government, Interactions Among Officials, Continuous and Cumulative Relationships, All Public Officials, and Policy Emphasis. The findings indicate that vertical intergovernmental collaboration has been institutionalized through the localization of national policies, cross-sectoral coordination mechanisms, integrated digital reporting systems, and full implementation of the allocated program budget. Nevertheless, coordination remains predominantly reactive, highlighting the need for more consistent intergovernmental communication and stronger integration of information systems to improve the effectiveness and sustainability of the PUSPAGA program.